Methods, Diagnostic Criteria, Cutoff Points, and Prevalence of Sarcopenia among Older People - Valéria Pagotto; Erika Aparecida Silveira (The Scientific World Journal)
Aim. To identify methods, index, diagnostic criteria, and corresponding cutoff points used to estimate the prevalence of sarcopenia in older people in different countries. Methods. A systematic review was carried out in accordance with PRISMA Statement. The search encompassed the MEDLINE and LILACS databases and was executed during March 2012 using the keyword sarcopenia. Results. A total of 671 studies were identified by the search strategy, and 30 meet all inclusion criteria. Specifically for dual-X-ray absorptiometry, prevalence ranged from 2.2% to 95% in men and from 0.1% to 33.9% in women. For bioelectrical impedance analysis, the range was from 6.2% to 85.4% in men and 2.8% to 23.6% in women. Regarding anthropometric and computed tomography, prevalence rates were, respectively, 14.1% and 55.9%. Conclusions. Heterogeneity in prevalence of sarcopenia was identified, due to diagnostic method choice, cutoff points, and, characteristics of the population as well as reference population. These factors should be considered in research designs to enable comparison and validation of results. Despite the limitations of most studies that indicated high prevalence rates, the results indicate the need for early detection of this syndrome.